MnO2 / rGO flexible transparent composite electrode film prepared by one-step electrodeposition and method
The preparation of MnO2/rGO composite electrode material on a gold grid by one-step electrodeposition method is solved, and the problem of poor stability and capacitance performance when manganese oxide and graphene are used alone in the prior art is solved, achieving an efficient and low-cost preparation process and excellent electrochemical performance.
Patent Information
- Application Number
- CN202510123750.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-14
AI Technical Summary
The existing supercapacitor electrode materials manganese oxide and graphene are used alone, and the composite material preparation process has high reaction temperature, high energy consumption, high cost, and difficult to control, and is not suitable for large-scale production.
The gold grid/MnO2/rGO flexible transparent composite electrode material was prepared by one-step electrodeposition method, and the MnO2/rGO composite material was deposited in one step on the surface of the gold grid by cyclic voltammetry, avoiding the tedious steps and high energy consumption of the traditional multi-step method.
It realizes the green pollution-free preparation raw materials, the fast and efficient preparation process, and the low-cost gold grid/MnO2/rGO flexible transparent composite electrode material, which improves electrochemical performance and cycle stability, and is suitable for large-scale production.
Smart Images

Figure CN119626795A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible transparent supercapacitors, and in particular relates to a gold grid / MnO2 / rGO flexible transparent composite electrode film prepared by one-step electrodeposition and a method thereof. Background Art
[0002] Supercapacitors are energy storage devices between traditional capacitors and traditional batteries. Compared with batteries, supercapacitors have the advantages of high power density, long cycle life, and high efficiency. Compared with traditional capacitors, they have the advantages of high energy density and long discharge time. In addition, supercapacitors themselves have the advantages of long storage life, wide operating temperature range, and environmental protection, making them very competitive in many fields, such as electric vehicles, hybrid vehicles, digital communication equipment, cameras, mobile phones, electronic tools, laser pulse technology, uninterruptible power supplies, solar energy storage devices, etc. Supercapacitor electrode materials mainly include carbon materials, conductive polymers, and transition metal oxides. Among them, carbon materials have the characteristics of wide sources, low prices, simple processing, non-toxicity, large specific surface area, good conductivity, good chemical stability, and wide applicable temperature. The energy density of metal oxides is greater than that of carbon materials and its electrochemical stability is better than that of conductive polymers. Therefore, graphene and manganese oxide are both very suitable as electrode materials, but graphene is easy to stack and agglomerate, which leads to its advantage of large specific surface area when used as electrode materials. This affects the electrochemical performance and limits the application of graphene. In addition, although manganese oxide itself has a high theoretical capacity, its actual capacity is far from reaching the theoretical capacity due to its poor cycle performance and weak conductivity. Therefore, the preparation of manganese oxide and graphene into composite materials for supercapacitors has attracted widespread attention from researchers and has become a research hotspot for supercapacitor electrode materials in recent years.
[0003] Existing preparation of MnO x @rGO composite electrode material is mainly prepared by a multi-step method. For example, CN107026026A discloses a three-step method for preparing MnO2 / rGO composite material as a supercapacitor electrode material, which first prepares manganese dioxide by a hydrothermal method, then hydrothermally reacts graphene oxide and manganese dioxide in a reactor to self-assemble into reduced graphene oxide-manganese dioxide hydrogel, and finally obtains reduced graphene oxide-manganese dioxide aerogel by freeze drying to be used as a supercapacitor electrode material. CN116544362A discloses a method for preparing MnO2 / rGO composite material as a supercapacitor electrode material by a two-step electrodeposition method. x The method of preparing the @rGO composite material comprises firstly depositing manganese oxide on a substrate by a constant current method, and then reducing and depositing graphene oxide on the manganese oxide by a constant current method to obtain MnO x@rGO composite material. The above preparation process has the problems of high reaction temperature, high energy consumption, high cost, difficult to control the reaction process and complicated process steps, and is not suitable for mass production applications. Summary of the invention
[0004] Purpose of the invention: In order to overcome the technical problems that manganese oxide and graphene alone have poor stability and capacitance performance as supercapacitor electrode materials, which seriously limit the development and application of supercapacitors, the preparation of composite materials has high reaction temperature, high energy consumption, high cost, difficult to control the reaction process, complicated process, and is not suitable for mass production and application, this application proposes a gold grid / MnO2 / rGO flexible transparent composite electrode material and method prepared by one-step electrodeposition, which can achieve green and pollution-free preparation of raw materials, convenient and fast preparation process, high deposition efficiency, and low-cost preparation of gold grid / MnO2 / rGO flexible transparent composite electrodes.
[0005] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition comprises the following steps: Step 1: Prepare a gold grid electrode; Step 2: preparing a graphene oxide / manganese acetate mixed solution; Step 3: Prepare MnO2 / rGO flexible transparent composite electrode by electrodeposition; Using a gold grid electrode as the working electrode, a platinum electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step 2 as the electrolyte, the MnO2 / rGO composite material is electrodeposited on the gold grid surface in one step by cyclic voltammetry; then the electrolyte adsorbed on the surface is washed to remove the electrolyte and dried to obtain a MnO2 / rGO flexible transparent composite electrode material.
[0006] Preferably: the method for preparing the gold grid electrode in step 1 is: plasma cleaning the PET substrate, then scraping an acrylic resin solution on the PET surface, and drying the sample to obtain an acrylic resin crack template; vacuum thermal evaporation deposits a gold film on the above-coated acrylic resin crack template, and then uses acetic acid to clean and remove the acrylic resin crack template to obtain a gold grid electrode.
[0007] Preferably: the method for preparing the graphene oxide / manganese acetate mixed solution in step 2 is: adding 100 mg-500 mg of graphene oxide to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersing it for 3-5 hours to obtain a graphene oxide dispersion; then, adding 2.29-3.43 g of manganese acetate to the graphene oxide dispersion and ultrasonically dispersing it for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0008] Preferably, the mass ratio of graphene oxide / manganese acetate in the graphene oxide / manganese acetate mixed solution in step 2 is 4.3 / 100-21.8 / 100.
[0009] Preferably, the potential interval of the cyclic voltammetry electrodeposition in step 3 is -1.4 V-1.2 V, the scan rate is 40 mV / s, the number of scans is 10-20, and the deposition time is 1300-2600 s.
[0010] Preferably: in step 3, deionized water is used to wash and remove the electrolyte adsorbed on the surface.
[0011] Preferably, in step 3, vacuum drying is performed at 50°C-70°C for 3-5 h.
[0012] The present invention also provides a MnO2 / rGO flexible transparent composite electrode film, which is prepared by the above-mentioned preparation method.
[0013] Preferably, the sheet resistance of the MnO2 / rGO flexible transparent composite electrode film is 40-160Ω / sq, and the transmittance is 50-72%.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. In the method for preparing MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition of the present invention, reduced graphene oxide and manganese dioxide are compounded, and a synergistic effect will be produced between them. On the one hand, the high conductivity of reduced graphene oxide can provide a good electron transmission channel for manganese dioxide, making up for the shortcoming of poor conductivity of manganese dioxide itself. On the other hand, the pseudocapacitive properties of manganese dioxide can increase the overall capacitance performance of the composite electrode material, and cooperate with the double-layer capacitance of reduced graphene oxide, so that the composite electrode material exhibits better performance in supercapacitors. The present invention adopts a one-step electrodeposition process to electrodeposit MnO2 / rGO composite electrode material on a substrate to prepare a gold grid / MnO2 / rGO flexible transparent composite material electrode with excellent performance.
[0015] 2. Since the electrolyte consists only of sodium sulfate, manganese acetate and GO, the use of hazardous chemicals is avoided, and the potential environmental pollution risks in the preparation process of composite materials are avoided.
[0016] 3. Since the electrode material is directly deposited on the substrate, the use of a binder to coat the electrode material on the current collector is avoided, thereby avoiding the influence on the composite electrode material. This is conducive to the synergistic effect between the composite materials and reduces the influence of the added components, thereby obtaining a MnO2 / rGO composite electrode material with excellent performance.
[0017] 4. It only requires one-step preparation using cyclic voltammetry through an electrochemical workstation, avoiding the cumbersome steps of traditional preparation methods. It has the advantages of simple preparation process, high deposition efficiency, strong repeatability, and lays a good foundation for the development of flexible transparent supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an optical microscope image of the MnO2 / rGO flexible transparent composite electrode film; Figure 2 This is a cyclic voltammetry curve of the MnO2 / rGO flexible transparent composite electrode film prepared in Example 1. DETAILED DESCRIPTION
[0019] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0020] Example 1 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0021] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 300 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0022] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 10 circles, and the deposition time was 1300 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 50 ℃ for 5 h to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0023] Example 2 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0024] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 100 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0025] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 10 circles, and the deposition time was 1300 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 70 °C for 3h to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0026] Example 3 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0027] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 200 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0028] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 10 circles, and the deposition time was 1300 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 60 °C for 4 hours to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0029] Example 4 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0030] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 500 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0031] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 10 circles, and the deposition time was 1300 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 60 °C for 4 hours to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0032] Example 5 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0033] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 300 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 3 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0034] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 10 circles, and the deposition time was 1300 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 60 °C for 4 hours to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0035] Example 6 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0036] Step S2: Preparation of graphene oxide / manganese acetate mixed solution 300 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide dispersion; then, 2.29 g of manganese acetate was added to the above graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
[0037] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition The gold grid electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step S2 was used as the electrolyte. The MnO2 / rGO composite material was deposited on the gold grid surface in one step by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 v-1.2 v, the scanning rate was 40 mV / s, the number of scanning circles was 20 circles, and the deposition time was 2600 s. The electrolyte adsorbed on the surface was washed with deionized water and vacuum dried at 60 °C for 4 hours to obtain the MnO2 / rGO flexible transparent composite electrode material (MnO2 / rGO flexible transparent composite electrode film).
[0038] Comparative Example 1 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0039] Step S2: Preparation of manganese acetate solution 2.29 g of manganese acetate was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 1 h to prepare a manganese acetate solution.
[0040] Step S3: Preparation of MnO2 flexible transparent composite electrode by electrodeposition Using a gold grid electrode as the working electrode, a platinum electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the manganese acetate solution prepared in step S2 as the electrolyte, the MnO2 material was electrodeposited on the gold grid surface by cyclic voltammetry. The potential range of the cyclic voltammetry electrodeposition was -1.4 V-1.2 V, the scanning rate was 40 mV / s, the number of scanning circles was 10, and the deposition time was 1300 s.
[0041] Comparative Example 2 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0042] Step S2: Preparation of graphene oxide solution 300 mg of graphene oxide was added into 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 h to prepare a graphene oxide solution.
[0043] Step S3: Preparation of rGO flexible transparent composite electrode by electrodeposition Using a gold grid electrode as the working electrode, a platinum sheet electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the graphene oxide solution prepared in step S2 as the electrolyte, the rGO material was electrodeposited on the gold grid surface by cyclic voltammetry. The potential interval of the cyclic voltammetry electrodeposition was -1.4 V-1.2 V, the scanning rate was 40 mV / s, the number of scanning circles was 10, and the deposition time was 1300 s.
[0044] Comparative Example 3 Step S1: Preparation of gold grid electrodes The PET substrate was plasma cleaned, and then an acrylic resin solution was scraped on the PET surface. After the sample was dried, an acrylic resin crack template was obtained. A 20 nm gold film was deposited on the acrylic resin crack template by vacuum thermal evaporation, and then the acrylic resin crack template was removed by cleaning with acetic acid to obtain a gold grid electrode. The square resistance of the obtained gold grid electrode is 2Ω / sq, and the transmittance is 84%.
[0045] Step S2: Preparation of graphene oxide solution and manganese acetate solution 300 mg of graphene oxide was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 5 hours to obtain a graphene oxide solution; 2.29 g of manganese acetate was added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 1 hour to obtain a manganese acetate solution.
[0046] Step S3: Preparation of MnO2 / rGO flexible transparent composite electrode by electrodeposition Using a gold grid electrode as the working electrode, a platinum electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the manganese acetate solution prepared in step S2 as the electrolyte, the MnO2 material is electrodeposited on the gold grid surface by cyclic voltammetry, and then the rGO material is electrodeposited on the gold grid surface by cyclic voltammetry using the graphene oxide solution prepared in step S2 as the electrolyte; the potential range of the cyclic voltammetry electrodeposition is -1.4 V-1.2 V, the scanning rate is 40 mV / s, the number of scanning circles is 10 circles, and the deposition time is 1300 s.
[0047] Performance test: The samples (1cm×1cm) prepared in the above-mentioned Examples 1-6 and Comparative Examples 1-3 were used as electrodes, and LiCl / PVA gel was used as the electrolyte and the diaphragm to assemble a symmetrical flexible transparent supercapacitor. The light transmittance of the monolithic electrode film and the symmetrical flexible transparent supercapacitor prepared in the above-mentioned Examples 1-6 and Comparative Examples 1-3 was tested using a UV-visible spectrophotometer. Cyclic voltammetry and constant current charge-discharge tests were performed on the assembled symmetrical flexible transparent supercapacitor using a two-electrode system on an electrochemical workstation. The voltage range of the device cyclic voltammetry test was -0.8-0.8V, and the scan rate was 10-100mV / s. The area specific capacitance at a scan rate of 10 mV / s was selected to compare the capacitance performance of the device; the voltage range of the constant current charge-discharge test was -0.8-0.8V, and the current density was 100, 150, 200, 300, 400, 500µA / cm 2 ,like Figure 1 , 2 As shown in Figure 2, the device rate performance is compared by comparing the area specific capacitance of the device at different current densities; at 500 µA / cm 2 The device was subjected to 2000 constant current charge and discharge tests at a current density of 1.5 to characterize the cycle stability of the symmetrical device after multiple charge and discharge cycles; the above-mentioned device was bent and folded at 60° for 500 times in sequence and then subjected to constant current charge and discharge tests, and the capacitance retention rate of the device before and after bending and folding was calculated.
[0048] Table 1 The specific test results are shown in Table 1. Comparing the samples of Example 1 and Comparative Example 1, in Comparative Example 1, only MnO2 was deposited on the gold grid. Due to the poor electrochemical stability of the MnO2 material, the capacity retention rate of the capacitor assembled into it after 2000 cycles was only 45.7%; at the same time, due to the low conductivity of MnO2, the electron transmission efficiency was not high in practical applications, and its capacitance performance was only 1.8 mF / cm 2 . In Example 1, the capacity retention rate was greatly improved to 94.2% by compounding MnO2 with rGO, and the area specific capacitance and bending resistance were also slightly improved. This shows that the introduction of rGO can significantly improve the electrochemical stability of manganese dioxide as an electrode material. Comparing the samples of Example 1 and Comparative Example 2, only rGO was deposited on the gold grid in Comparative Example 2. Although the capacity retention rate of the sample assembled into a supercapacitor reached 95.7% after 2000 cycles, its area specific capacitance was only 0.32mFcm -2 ; It shows that manganese dioxide helps to improve the capacity of supercapacitors. Comparing the samples of Example 1 and Comparative Example 3, Comparative Example 3 replaces the one-step electrodeposition method with a two-step electrodeposition method. Since the distributed electrodeposition method will cause problems such as poor interface contact, its cycle performance and bending resistance performance are significantly reduced. In addition, due to the large amount of rGO deposited on the surface of manganese dioxide, the pseudocapacitive performance of manganese dioxide is difficult to fully exert, and its capacitance performance is significantly reduced, only 4.2 mF / cm 2 . Compared with Example 2, Example 3, and Example 4, the concentration of deposited liquid graphene oxide in Example 1 is lower than that in Example 4, but higher than that in Example 2 and Example 3; the ranking of area specific capacitance after the sample is assembled into devices is Example 2 < Example 3 < Example 1 < Example 4, and the ranking of transmittance and cycle performance is just the opposite, Example 2 > Example 3 > Example 1 > Example 4; this shows that the concentration of graphene oxide mainly affects the capacitance performance of the supercapacitor, the transmittance of the battery, and the long cycle performance; the higher the concentration, the more rGO is deposited, the better the cycle performance, and the higher the coverage of the composite material, which also leads to lower transmittance. Compared with Example 5, Example 1 is uniformly ultrasonically dispersed during the preparation of the graphene oxide solution, avoiding the uneven local deposition caused by precipitation caused by standing during the deposition process. Compared with Example 6, the time for depositing the sample in Example 1 is short, and the capacity and electrochemical properties are inversely proportional to the transmittance, which also shows that the more the composite material is deposited, the better the electrochemical performance and the worse the transmittance.
[0049] In summary, the electrode prepared by the method for preparing the gold grid / MnO2 / rGO flexible transparent composite electrode material by one-step electrodeposition proposed in the present invention has the advantages of good light transmittance, good cycle performance, good capacitance performance, etc. In addition, it only needs to be prepared in one step by using cyclic voltammetry in an electrochemical workstation, avoiding the cumbersome steps of the traditional preparation method, and has the advantages of simple preparation process, high deposition efficiency, strong repeatability, and good development prospects. The prepared MnO2 / rGO flexible transparent composite electrode material has high flexibility, high light transmittance, high capacity and cycle stability, and has great application potential in the field of flexible transparent energy storage.
[0050] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition, characterized in that: The following steps are involved: Step 1: Prepare a gold grid electrode; Step 2: preparing a graphene oxide / manganese acetate mixed solution; Step 3: Prepare MnO2 / rGO flexible transparent composite electrode by electrodeposition; Using a gold grid electrode as the working electrode, a platinum electrode as the counter electrode, a saturated calomel electrode as the reference electrode, and the graphene oxide / manganese acetate mixed solution prepared in step 2 as the electrolyte, the MnO2 / rGO composite material is electrodeposited on the gold grid surface in one step by cyclic voltammetry; then the electrolyte adsorbed on the surface is washed to remove the electrolyte and dried to obtain a MnO2 / rGO flexible transparent composite electrode material.
2. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 1, characterized in that: The method for preparing the gold grid electrode in step 1 is as follows: plasma cleaning the PET substrate, then coating the PET surface with an acrylic resin solution, and drying the sample to obtain an acrylic resin crack template; vacuum thermal evaporation depositing a gold film on the acrylic resin crack template, and then using acetic acid to clean and remove the acrylic resin crack template to obtain a gold grid electrode.
3. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 2, characterized in that: The method for preparing the graphene oxide / manganese acetate mixed solution in step 2 is as follows: 100 mg-500 mg of graphene oxide is added to 100 mL of Na2SO4 aqueous solution and ultrasonically dispersed for 3-5 hours to obtain a graphene oxide dispersion; then, 2.29-3.43 g of manganese acetate is added to the graphene oxide dispersion and ultrasonically dispersed for 1 hour to obtain a graphene oxide / manganese acetate mixed solution.
4. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 3, characterized in that: The mass ratio of graphene oxide / manganese acetate in the graphene oxide / manganese acetate mixed solution in step 2 is 4.3 / 100-21.8 / 100.
5. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 4, characterized in that: The potential interval of the cyclic voltammetry electrodeposition in step 3 is -1.4 V-1.2 V, the scanning rate is 40 mV / s, the number of scanning circles is 10-20 circles, and the deposition time is 1300-2600 s.
6. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 5, characterized in that: In step 3, deionized water is used to wash and remove the electrolyte adsorbed on the surface.
7. The method for preparing a MnO2 / rGO flexible transparent composite electrode film by one-step electrodeposition according to claim 6, characterized in that: In step 3, vacuum drying is performed at 50°C-70°C for 3-5 h.
8. A MnO2 / rGO flexible transparent composite electrode film, characterized in that: The preparation method is described in any one of claims 1 to 7.
9. The MnO2 / rGO flexible transparent composite electrode film according to claim 8, characterized in that: The sheet resistance of the MnO2 / rGO flexible transparent composite electrode film is 40-160Ω / sq and the transmittance is 50-72%.
Citation Information
Patent Citations
Transparent electrically conductive film, method for manufacturing transparent electrically conductive film, photoelectric conversion device and electronic equipment
CN103155051A
Preparation method of flexible electrode material
CN104362326A
Method for preparing high-performance metallic network transparent conducting electrode through metal plating method
CN105350043A
KR20210122945A